2014 Makassar International Conference on Electrical Engineering and Informatics (MICEEI) 2014
DOI: 10.1109/miceei.2014.7067325
|View full text |Cite
|
Sign up to set email alerts
|

The simulation of vehicle counting system for traffic surveillance using Viola Jones method

Abstract: Traffic congestion in Makassar has occurred over the last 3 years due to the increase of vehicle amount with the lack of adequate road space. To solve the problem, the Intelligent Transportation System (ITS) is needed. One of the research topics in ITS is determining the turnover time of traffic lights based on the number of vehicles in the road. Viola-Jones method can be used to count the number of vehicles by detecting objects. Therefore, this study shows a simulation of the number of vehicles using the Viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…Furthermore, previous research for vehicle counting but different method studied by Indrabayu, et al which used Viola Jones in examining accuracy effect by the number of samples. The research found highest detection accuracy was 92% [4].…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, previous research for vehicle counting but different method studied by Indrabayu, et al which used Viola Jones in examining accuracy effect by the number of samples. The research found highest detection accuracy was 92% [4].…”
Section: Introductionmentioning
confidence: 83%
“…Traditional computer image processing programs allow transformations or beautification of digital images only, due to this, software-based applications have been devised to increase the amount of operations available to users to understand the information that an image provides. Some of these applications allow information to be recovered by reconstructing the image based on assumptions or eliminating characteristics that attenuate the information of interest [2][3][4][5].…”
Section: Preparation and Processing Of A Digital Imagementioning
confidence: 99%
“…The most common way to estimate the values of a histogram is based on: decreasing the number of dimensions of the image by converting its color format to gray scale and estimating the frequencies with the expression shown in (1). Where the dimensions are w (width) and h (height), n represents the gray levels and 𝑁 𝑛𝑔 is the number of pixels [5].…”
Section: Preparation and Processing Of A Digital Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Dewiani Djamaluddin ve arkadaşları trafik yoğunluğunu ölçebilmek için VJ nesne tanıma algoritmasından faydalanmışlardır [7]. Özellikle benzer ve simetrik içeriklere sahip taşıtların ön kısımlarından alınan az sayıdaki örnek fotoğraflar ile %92 başarılı tespit oranına erişilmiştir.…”
Section: Introductionunclassified